Acceleration and focusing of electron bunches by wakefields in plasma produced in neutral gas by a nonresonant sequence of bunches - Kiselev, V.A.; Linnik, A.F.; Onishchenko, I.N.; Pristupa, V.I. (Вопросы атомной науки и техники, 2012)
It is experimentally investigated the possibility of accelerating and focusing of relativistic electron bunches by wakefields excited by their sequence in plasma, produced during its passage through the neutral gas, caused by the displacement of bunches into corresponding phases of excited field in the presence of mismatch between the bunch repetition frequency and plasma frequency. The mismatch is achieved by changing the pressure of the neutral gas at a fixed beam current density. Energy loss of some bunches and energy gain of others in the presence of other mismatch are estimated from the energy spectrum obtained from the imprints on the glass plate of bunches deflected with the transverse magnetic field. Focusing/defocusing of electron bunches is demonstrated by the change of the transverse sizes of imprints of nondeflected bunches and corresponding temporal modulation of the axial current density of the beam measured by Faraday cup of small cross-section Экспериментально исследована возможность ускорения и фокусировки релятивистских электронных сгустков кильватерными полями, возбуждаемыми их последовательностью в плазме, создаваемой при ее прохождении через нейтральный газ и обусловленной смещением сгустков в соответствующие фазы возбуждаемого поля при наличии расстройки между частотой следования сгустков и плазменной частотой. Расстройка достигалась изменением давления нейтрального газа при неизменной плотности тока пучка. Потери энергии одних сгустков и ускорение других при наличии расстройки оценивались по энергетическому спектру, полученному из отпечатков на стеклянной пластине сгустков, отклоненных поперечным магнитным полем. Фокусировка/дефокусировка электронных сгустков демонстрируется изменением поперечных размеров отпечатков неотклоненных сгустков и соответствующей временной модуляцией осевой плотности тока пучка, измеренной цилиндром Фарадея малого сечения. Експериментально досліджена можливість прискорювання і фокусування релятивістських електронних згустків кільватерними полями, збуджуваними їх послідовністю у плазмі, створюваної при її проходженні через нейтральний газ і обумовленої зміщенням згустків у відповідні фази збуджуваного поля при наявності розстройки між частотою слідування згустків і плазмовою частотою. Розстройка досягалась зміною тиску нейтрального газу при постійній щільності струму пучка. Втрати енергії одних згустків і прискорення інших при наявності розстройки оцінювались з енергетичного спектру, отриманому з відбитків на скляній пластині згустків, відхилених поперечним магнітним полем. Фокусування/дефокусування електронних згустків демонструється зміною поперечних розмірів відбитків невідхилених згустків і відповідною часовою модуляцією осьової щільності струму пучка, виміряної циліндром Фарадея малого перетину.